The Effect of Environmentally Friendly Packaging and Product Labeling on Purchasing Decisions and Business Sustainability of MSMEs in Bogor - Mohammad Gifari Sono; Apriyanto Apriyanto; Paramita Andiani (West Science Social and Humanities Studies, 2025)
This study investigates the impact of Environmentally Friendly Packaging (EFP) and Product Labeling (PLA) on Purchasing Decisions (PDE) and Business Sustainability (BSU) in Micro, Small, and Medium Enterprises (MSMEs) in Bogor, Indonesia. Using a quantitative approach, data were collected from 170 MSME owners and analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS). The results show that EFP and PLA have significant positive effects on PDE and BSU. Specifically, EFP influences Purchasing Decisions (β = 0.358, p < 0.001) and Business Sustainability (β = 0.240, p = 0.003), while PLA strongly affects both Purchasing Decisions (β = 0.530, p < 0.001) and Business Sustainability (β = 0.487, p < 0.001). These findings suggest that MSMEs can improve their competitiveness and long-term viability by adopting eco-friendly packaging and emphasizing sustainable labeling practices. The study contributes to the understanding of sustainable business practices in the context of MSMEs and provides valuable insights for entrepreneurs aiming to enhance their market position and ensure sustainability.